Crop genetic resources in European home gardens: Proceedings of a workshop, 3-4 October 2007, Ljubljana, Slovenia - Bailey, Arwen; Eyzaguirre, Pablo B.; Maggioni, L. (2009)
These proceedings relate to a workshop on home gardens that was organized in Ljubljana, Slovenia, 3-4 October 2007 by the ECPGR In situ and On-farm Conservation Network. The opportunity to convene nearly fifty scientists working on home gardens in a regional meeting was based on the awareness that home gardens probably constitute the richest agro-ecosystems in Europe in terms of genetic diversity of agricultural crops.At the same time, there is incomplete information on the actual composition of home gardens and on the trends that may affect the maintenance of these precious but possibly fragile ecosystems in the near future. The workshop intended to collect information on home gardens composition, status and distribution in Europe; the role of home gardens for the conservation of diversity; incentives and policies. It also aimed at defining ways to bring forward research, assessing possibility of forming networks and raising awareness. This book collects together a number of the contributions that were made in Ljubljana and intends to be a starting point demonstrating the opportunity to join efforts to understand and maintain precious resources in Europe.